From Cradle to Grave: How Childhood and Current Environments Impact Consumers’ Subjective Life Expectancy and Decision-Making - Mittal, Chiraag; Griskevicius, Vladas; Haws, Kelly L (Journal of Consumer Research, 2020)
The age to which people expect to live likely drives many important consumer decisions. Yet we know surprisingly little about the antecedents and consequences of consumers’ subjective life expectancies. In the present work, we propose that subjective life expectancy is influenced by the combination of people’s childhood environment and their current environment. We find that people who grew up in poorer environments expected to have a shorter lifespan compared to people who grew up in richer environments when faced with a current stressor. We document that experiencing a stressor leads people from resource-poor childhoods to believe they will die sooner because they respond to stressors in a more pessimistic way. We further show that subjective life expectancy is an important psychological mechanism that directly contributes to multiple consumer decisions, including desire for long-term care insurance, decisions about retirement savings, and preference for long-term bonds. Overall, the present work opens future research avenues by showing how, why, and when subjective life expectancy influences consumer behavior.